A Course in distribution theory and applications - Pathak, R.S. (Alpha Science International, 2001)
This book provides a systematic exposition of the basic ideas and results of distribution theory and its applications to Fourier analysis and partial differential equations without using much sophisticated concepts of functional analysis. The book covers important topics: basis properties of distributions, convolution, Fourier transforms, Sobolev spaces, weak solutions, distributions on locally convex spaces and on differentiable manifolds.